Tripod Missions: Five Principles for Solving Society's Most Pressing Challenges - David Bach; Henning Meyer (Global Policy, 2022)
The COVID crisis has forced policymakers to design new and comprehensive rescue programmes under huge time pressure. This task has required innovative policy thinking and the pursuit of new kinds of collaboration. The handling of the pandemic, however, also provides valuable lessons on how to address some of society's other pressing challenges—above all climate change. 'Tripod Missions' provide a framework for turning the pandemic's lessons learned into a guide for tackling other major societal problems.
Keywords: 320